2020
DOI: 10.3390/pr8070823
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Copper in Stems and Roots of Jatropha curcas L. by Hyperspectral Imaging

Abstract: The in situ determination of metals in plants used for phytoremediation is still a challenge that must be overcome to control the plant stress over time due to metals uptake as well as to quantify the concentration of these metals in the biomass for further potential applications. In this exploratory study, we acquired hyperspectral images in the visible/near infrared regions of dried and ground stems and roots of Jatropha curcas L. to which different amounts of copper (Cu) were added. The spectral information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…However, as well known, these methods are expensive, are time-consuming, require highly specialized staff, are destructive, and do not allow in-field analysis. Other alternative strategies for the copper residue detection in plants based on the use of imaging techniques have been proposed in literature in few exploratory studies (García-Martín et al, 2020;Goswami & Das, 2017;Mijovilovich et al, 2020;Zeng et al, 2019). However, compared to the imaging approach that we implement in this work, these methods require analyses both in spectral ranges and with operational protocols more complicated and expensive and which is difficult to implement a prototype monitoring system that works in field.…”
Section: Resultsmentioning
confidence: 99%
“…However, as well known, these methods are expensive, are time-consuming, require highly specialized staff, are destructive, and do not allow in-field analysis. Other alternative strategies for the copper residue detection in plants based on the use of imaging techniques have been proposed in literature in few exploratory studies (García-Martín et al, 2020;Goswami & Das, 2017;Mijovilovich et al, 2020;Zeng et al, 2019). However, compared to the imaging approach that we implement in this work, these methods require analyses both in spectral ranges and with operational protocols more complicated and expensive and which is difficult to implement a prototype monitoring system that works in field.…”
Section: Resultsmentioning
confidence: 99%
“…In general, leaves were more likely to be used for plant phenotyping. Fewer studies have studied the high-throughput phenotyping of stems [66][67][68][69][70][71][72][73]. The overall results showed that stems can be an efficient alternative for plant phenotyping in addition to leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its rapidity, high efficiency, and nondestructivity, near-infrared (NIR) spectroscopy has been used widely in biological, , petrochemical, pharmaceutical, agricultural, and food-processing , applications. NIR spectroscopy is also effective in the quantitative analysis of tobacco components. ,, Chemical models for components having high contents, such as total sugar (TS), reducing sugar (RS), total nitrogen (TN), nicotine (NIC), and chlorine (Cl), are relatively robust. , However, the performance of trace-component models may be subideal. , Furthermore, models of organic acids, amino acids, and Amadori compounds have rarely been reported, although these compounds critically influence the unique style of tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its rapidity, high efficiency, and nondestructivity, near-infrared (NIR) spectroscopy has been used widely in biological, 8 , 9 petrochemical, 10 pharmaceutical, 11 agricultural, 12 14 and food-processing 15 , 16 applications. NIR spectroscopy is also effective in the quantitative analysis of tobacco components.…”
Section: Introductionmentioning
confidence: 99%